Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Negeri Sipil (PNS) Pada Bagian Hubungan Masyarakat (Humas) Sekretariat Daerah Kabupaten Kaimanaa - Paskalis Janoma; Nurtisatul Mukarramah (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of work motivation and job satisfaction on the performance of Civil Servants (PNS) in the Public Relations (HUMAS) Division of the Regional Secretariat of Kaimana Regency. Motivation and job satisfaction factors are considered as important elements influencing employee performance. The research method used is quantitative with a correlational approach. The sample consists of 20 PNS employees from the HUMAS Division, selected using purposive sampling technique. Data were collected through questionnaires and processed using multiple linear regression to examine the effect of each independent variable (work motivation and job satisfaction) on the dependent variable (PNS performance).The results of the study show that work motivation has a positive and significant effect on PNS performance with a contribution of 23.1%, while job satisfaction has a greaterinfluence, contributing 84.1%. Simultaneously, both independent variables contribute significantly to PNS performance, with a coefficient of determination value of 69.6%, indicating that work motivation and job satisfaction together contribute to improving employee performance. The remaining 30.4% is influenced by other factors not included in this study.This study is expected to provide insights into improving PNS performance through effective management of work motivation and job satisfaction.